Influence of Ozone on the Biochemical Composition of Birch Sap - Simona Paulikienė (Applied Sciences, 2021)
Studies have shown that ozone is a good oxidizer and a strong disinfectant. There are many uses for ozone in the food industry, but there is relatively little information about the influence of ozone on biochemical composition and the capacity to reduce the number of microorganisms in birch sap. In this study, sap was ozonated at different intervals for 5 min (O3: 0.087 ± 0.009 mg L−1), 10 min, 15 min, 20 min, 25 min, or 30 min (O3: 0.99 ± 0.09 mg L−1). The parameters of the birch sap were studied immediately after the ozone treatment as well as during storage for seven days at 2 °C and for five days at 20 °C. The parameters of ozonated birch sap were compared with the parameters of fresh sap (control). The microbiological analysis included total bacterial count, lactic acid bacterial count, and yeast and mold count. Birch sap color, pH, titratable acidity, and ºBrix values were also determined. Evaluation of monosaccharides, sucrose, total sugars, and ascorbic acid was carried out in fresh sap as well as sap ozonated for 30 min, immediately after ozonation. The results show the statistical significance of the inactivation of microorganisms after treatment in most cases. The microorganism counts gradually reduced with increasing intervals of ozone treatment. The best results were obtained after 25 and 30 min of ozonation. Ozone treatment did not significantly influence the pH, titratable acidity, or °Brix statistically. Values of monosaccharides, sucrose, total sugars, and ascorbic acid were influenced within the margin of error. Ozone had a significant influence on the chroma and hue angle.